2019
DOI: 10.15406/ncoaj.2019.06.00179
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in health and social care services to older adults living with HIV: a qualitative study on the perspectives of older adults and service providers

Abstract: Medical and social science research on older adults living with HIV (OAHIV) has shed light on the significant health needs and the many psychosocial difficulties experienced by this population. Despite the obvious need for health and social care services among OAHIV, few studies have addressed their experiences with regard to these resources. This study attempts to identify the challenges, difficulties and gaps found within social and health services intended for those located at the intersection of HIV and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A significant source of uncertainty is how needs will be met if participants become unable to live independently, as previously documented [ 18 ]. Many reject long‐term care or seniors’ housing for fear of HIV stigma and/or homophobia [ 9 , 51 , 52 ]. Although we did not hear many examples, the literature documents experiences of discrimination in healthcare and other institutional settings as common among older PLWH [ 14 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant source of uncertainty is how needs will be met if participants become unable to live independently, as previously documented [ 18 ]. Many reject long‐term care or seniors’ housing for fear of HIV stigma and/or homophobia [ 9 , 51 , 52 ]. Although we did not hear many examples, the literature documents experiences of discrimination in healthcare and other institutional settings as common among older PLWH [ 14 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the stigma and marginalization that can be found in non-specialist services [ 17 ]. Difficulties in transitioning between the different services and gaps in these services for PLWH have likewise been found [ 3 , 19 ], meaning that PLWH have to balance who would best meet their needs and help them maintain their QoL while having to cope with the possibility of a negative experience.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults also tend to not access social services designed for the HIV-infected population because of their own assumption that these programs are created only for younger individuals [ 22 ]. Consequently, HIV scholars have urged for a health and social care system where knowledge and communication about geriatric HIV care are encouraged amongst advocates who work directly with this population, such as geriatric healthcare workers [ 23 ].…”
Section: Introductionmentioning
confidence: 99%